Some Important Applications of Using Sodium Alginate: Review - Shaimaa A. Hassan; Abd, Ahmed N. (ASJ - Academic Science Journal, 2025)
Alginate is a biological substance with a wide range of uses in engineering and the biological sciences. Its exceptional qualities, namely its excellent biocompatibility and simple gelling, make it widely employed. Numerous cross-linking methods, for example, can be used to create alginate hydrogels. Their structural similarity to extracellular matrices present in living tissues makes them highly useful for wound healing as well as the administration of chemical medicines, tiny proteins, and transplanted cells. Alginate is also frequently employed in a variety of technologies, such as tissue engineering cell transplantation and different biomolecule immobilization techniques. This study will address the main features of alginate and hydrogels, their biological functions, and new ways to research with these polymers in the future.